2020
DOI: 10.1093/mnras/staa3777
|View full text |Cite
|
Sign up to set email alerts
|

RoboPol: AGN polarimetric monitoring data

Abstract: We present uniformly reprocessed and re-calibrated data from the RoboPol programme of optopolarimetric monitoring of active galactic nuclei (AGN), covering observations between 2013, when the instrument was commissioned, and 2017. In total, the dataset presented in this paper includes 5068 observations of 222 AGN with Dec > −25○. We describe the current version of the RoboPol pipeline that was used to process and calibrate the entire dataset, and we make the data publicly available for use by the astron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 57 publications
4
45
0
Order By: Relevance
“…uary 3 and 2019 August 4. The 49 new AGN included here are members of either the Robopol optical polarization survey (Blinov et al 2021), the Fermi 2FHL catalog (Ackermann et al 2016), the LAT monitored list of flaring sources 3 , or the MOJAVE-Fermi hard spectrum gamma-ray sample (Lister et al 2018).…”
Section: Mojave Data Archivementioning
confidence: 99%
“…uary 3 and 2019 August 4. The 49 new AGN included here are members of either the Robopol optical polarization survey (Blinov et al 2021), the Fermi 2FHL catalog (Ackermann et al 2016), the LAT monitored list of flaring sources 3 , or the MOJAVE-Fermi hard spectrum gamma-ray sample (Lister et al 2018).…”
Section: Mojave Data Archivementioning
confidence: 99%
“…The spread of the reported proper motions is rather large. In our study (Blinov et al 2021a) we found that the ratios of 𝛿 for individual components can change up to a factor ∼ 5. Assuming a larger Doppler factor will only tighten the constraints on 𝐵 and 𝑓 .…”
Section: Discussionmentioning
confidence: 45%
“…A fraction of them shows rotations of the optical polarization plane that are most often accompanied by bright outbursts across the electromagnetic spec-★ E-mail: yannis.liodakis@utu.fi trum (Marscher et al 2008(Marscher et al , 2010Bottacini et al 2016;Raiteri et al 2017a;Uemura et al 2017;Blinov et al 2021b). While their optical and radio linear polarization (LP) properties have been getting plenty of attention lately (e.g., Kovalev et al 2020;Kravchenko et al 2020;Blinov et al 2021a;Event Horizon Telescope Collaboration et al 2021;Goddi et al 2021), their optical circular polarization (CP) properties are unexplored. This is partly because of the scarcity of instruments capable of delivering CP measurements, but also because CP is expected to be low even in optimistic scenarios, requiring very sensitive instruments.…”
Section: Introductionmentioning
confidence: 99%
“…0059+581 has been used as a bright and compact fringe finder during VGOS commissioning work. It does however exhibit significant flux density variability on short and long timescales, and has been included in multiple monitoring campaigns at radio (Lister et al, 2018(Lister et al, , 2021, gamma-ray (Paliya et al, 2021) and optical (Blinov et al, 2021) wavelengths. This source was the one most often included in our monitoring, already from the start and our FM-results are shown in Fig.…”
Section: +581mentioning
confidence: 99%